1994
DOI: 10.1017/s0016756800012450
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Ordovician deformation in southeast Ireland: evidence from the geological setting, geochemical affinities and U—Pb zircon age of the Croghan Kinshelagh granite

Abstract: The Croghan Kinshelagh alkali granite intrudes a cleaved volcano-sedimentary sequence on the border of counties Wicklow and Wexford in southeast Ireland. U-Pb dating of zircons from the granite indicate a mid-Caradoc emplacement age of 454+ 1 Ma. The Duncannon Group host rocks form the southwestern end of the Avoca Volcanic Belt, a Mid-Ordovician (Caradoc) sequence of acid and intermediate lavas and volcaniclastics. Dolerite dykes intrude the granite; elsewhere in the region dolerites are generally associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Chemical characteristics of the granites and volcanic rocks suggest that during their formation, the Leinster region was in a transitional position between a volcanic island arc that extended from County Waterford to the English Lake District and a back-arc basin in North Wexford -Wicklow. Gallagher et al (1994) demonstrated that the Croghan Kinshelagh Granite (Figs. 2 and 3; Croghan Complex of recent literature), cropping out west of the Goldmines River, is an older intrusion than the Leinster Granite.…”
Section: Geological Backgroundmentioning
confidence: 98%
See 2 more Smart Citations
“…Chemical characteristics of the granites and volcanic rocks suggest that during their formation, the Leinster region was in a transitional position between a volcanic island arc that extended from County Waterford to the English Lake District and a back-arc basin in North Wexford -Wicklow. Gallagher et al (1994) demonstrated that the Croghan Kinshelagh Granite (Figs. 2 and 3; Croghan Complex of recent literature), cropping out west of the Goldmines River, is an older intrusion than the Leinster Granite.…”
Section: Geological Backgroundmentioning
confidence: 98%
“…In the lower Ordovician, thick laminated mudstones were deposited: the striped appearance of these gave rise to the name 'Ribband Group'. The Cambrian and lower Ordovician strata were deformed in mid-Ordovician time by an orogenic event, the Monian, which was localised to the Leinster region and affected the southeast of the region more intensely than the northwest (Tietzsch-Tyler et al, 1994;Gallagher et al, 1994). In the upper Ordovician, further sediments and volcanic formations were deposited on the submerging Monian landmass, forming the Duncannon Group.…”
Section: Geological Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…It is likely that the D1 in the Ordovician Manx Group, similar in all respects to that in the Niarbyl Formation, is the same age, although an older, possibly Ordovician, age cannot be ruled out (cf. Gallagher et al 1994;Tietzsch-Tyler 1996). The D1 structures are very similar to the main structures described from other parts of the southern Caledonides of Britain, folds having a 'Caledonoid' trend, generally upright axial planes and horizontal plunge.…”
Section: D1 Deformationmentioning
confidence: 99%
“…Ireland, 1990) are succeeded by early Ordovician greywacke siltstones, mudstones and minor volcanic units (the Ribband Group), late Ordovician acidic volcanic deposits and mudstones (the Duncannon Group), and Silurian greywacke sandstones (the Kilcullen Group) overlying the suture zone of the closed ocean (Hutton & Murphy, 1987). Ordovician tectonic deformations (Tietzsch-Tyler, 1989;Gallagher, O'Connor & Aftalion, 1994), possible accretion events, were succeeded by early Devonian continental collision and orogenesis (Hatcher, 1988), during which the Leinster Granite (404 ± 2 Ma; O'Connor, Aftalion & Kennan, 1989) was intruded. The Lower Palaeozoic inliers of Wales and the English Lake District have broadly similar geological histories, and plate tectonic models of a Caledonian-trending Leinster-Lake District volcanic arc with a Welsh back-arc basin have been proposed (e.g.…”
Section: Introductionmentioning
confidence: 99%